Diversity-oriented synthesis of chromenopyrrolidines from azomethine ylides and 2-hydroxybenzylidene indandiones via base-controlled regiodivergent (3+2) cycloaddition. Issue 71 (17th August 2018) - Yu, Jhen-Kuei; Chien, Han-Wei; Lin, Yi-Jung; Karanam, Praneeth; Chen, Yu-Heng; Lin, Wenwei
Abstract : An organobase-controlled, regiodivergent (3+2) cycloaddition resulting in two different cascade reactions is demonstrated from azomethine ylides and 2-hydroxybenzylidineindandiones to achieve diverse chromanopyrrolidines. Abstract : An organobase-directed, regiodivergent 1, 3-dipolar cycloaddition of azomethine ylides and 2-hydoxybenzylidene indandiones is reported. The scarcely explored reversal of the nucleophilic site in azomethine ylides has been exploited for their regiodivergent (3+2) cycloaddition, which subsequently resulted in two different cascade processes to generate functionally distinct chromenopyrrolidines in a diversity oriented manner.